2019
DOI: 10.1021/acsanm.9b00758
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Organic–Organic Poly(vinylpyrrolidone) Microparticles and Fibers with Multiwalled Carbon Nanotubes for Reinforced Composites

Abstract: Polymeric-based microparticles and fibers are tailorable for a wide range of common industrial and biomedical applications, while multiwalled carbon nanotubes (MWCNTs) are among the most useful macromolecules based on their outstanding electronic, mechanical, and optical properties at the nanoscale. If one combines these nanostructures with various polymeric precursors, their range of potential applications becomes even greater. One of the simplest and most affordable methods for fabricating micro- and nanostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The Raman features from PVA nor PVDF are not observed, which is consistent with the literature, because in graphitic materials, the Raman process is resonant and so its signal is much more intense than the nonresonant signal from PVA and PVDF. [31,33,34] These findings clearly indicate that the structure of the FLG flakes is conserved in the final nanocomposite. [35][36][37] 3.2.…”
Section: Raman Spectroscopymentioning
confidence: 83%
“…The Raman features from PVA nor PVDF are not observed, which is consistent with the literature, because in graphitic materials, the Raman process is resonant and so its signal is much more intense than the nonresonant signal from PVA and PVDF. [31,33,34] These findings clearly indicate that the structure of the FLG flakes is conserved in the final nanocomposite. [35][36][37] 3.2.…”
Section: Raman Spectroscopymentioning
confidence: 83%
“…Electrospinning is one of the most appealing technologies for the incorporation of CDs within micro-/nanofibers and mats. This low-cost technique allows the transformation of a given viscoelastic fluid into fibrous membranes under the influence of an electric field and was observed for the first time more than a century ago [ 116 , 117 ]. The final performance of these fibrous materials is influenced by the physicochemical properties of the precursor solution, the experimental variables used during the electrospinning, and the environmental conditions.…”
Section: Methods Of Incorporating Cds In Polymer-based Active Food Packagingmentioning
confidence: 99%
“…Electrospinning has been used for nanofiber fabrication and modulate the nanostructure properties, namely larger surface area, small interstitial spaces, porous structure and fiber-connectivity. It was found that hydrophilicity properties of eggshell and silk nanofibers can be tuned by changing the ratio between both nanofibers in nanocomposites [ 111 , 122 ]. Modifications on the nanocomposite ratio resulted in changes in the water contact angle, which is associated with the wettability of the nanofibers [ 111 ].…”
Section: Prevention Of Covid-19 Infection Using Biomedical Sciencementioning
confidence: 99%